2017
DOI: 10.1590/1981-22562017020.170062
|View full text |Cite
|
Sign up to set email alerts
|

Medication use by the elderly: analysis of prescribing, dispensing, and use in a medium-sized city in the state of São Paulo

Abstract: Objective: To describe the prescribing, dispensing, use, adhesion, and storage of medicines to and by the elderly. Method: A descriptive cross-sectional study was performed in Estratégia Saúde da Família (Family Health Strategy) health centers (ESF), in Marília in the state of São Paulo, Brazil, based on the records of and interviews with 114 individuals seven to ten days after a medical consultation. A descriptive analysis was carried out. Results: The mean number of prescribed drugs was 4.98 per elderly pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
2
1
1
4
Order By: Relevance
“…Regarding sociodemographic characteristics, there was a predominance of those with older age and females, as verified in other studies published in the literature 7,8,20 . These factors may also be related to the prevalence of the use of medications and groups corroborating other studies that bring the same groups, although with different percentages 7,8,20,29 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Regarding sociodemographic characteristics, there was a predominance of those with older age and females, as verified in other studies published in the literature 7,8,20 . These factors may also be related to the prevalence of the use of medications and groups corroborating other studies that bring the same groups, although with different percentages 7,8,20,29 .…”
Section: Discussionsupporting
confidence: 83%
“…The number of antibiotics prescribed in the current study (0.3%) complied with the recommended value of less than 30% 9 . Thus, when comparing to other studies, the value was below those found by Stefano et al 8 , 21.4% and Berbigier et al 20 , 12.13%. The indicator regarding the prescription of injectable drugs, recommending prescription percentages below 20% 9 , like in present study reached.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…O estudo transversal foi o único tipo de pesquisa epidemiológica encontrada e não foram todos os autores 10,13,15,16,18 que apresentaram as medidas de associação esperadas para estudos com esse delineamento. Além disso, o estudo 16 conduzido em Marília (SP) se restringiu a análise descritiva dos achados, o que impossibilitou a verificação de qualquer associação, independente da natureza, ao desfecho.…”
Section: Discussionunclassified